ECONOMIC VIOLENCE IN THE FAMILY IN ISRAEL: AN INVISIBLE FORM OF CONTROL AND THE ETHICAL RESPONSIBILITY OF THE STATE WHEN CONTROL OVER MONEY BECOMES CONTROL OVER LIFE - Balous, Lulu (E-Journal VFU, 2025)
Economic violence, also known as economic or financial abuse, is a pervasive yet often invisible form of domestic violence that operates through systematic control of financial resources, access to employment, and economic decision-making. While lacking the overt physical markers associated with other forms of abuse, economic violence profoundly undermines individual autonomy, dignity, and long-term security. Existing research demonstrates that economic control frequently functions as a central mechanism of coercive power within abusive relationships, restricting victims’ ability to seek help or exit harmful environments. In the Israeli context, economic violence remains insufficiently recognized within legal, social, and institutional frameworks. Despite growing awareness of domestic violence more broadly, financial abuse is often normalized, culturally obscured, or misclassified as a private financial dispute. Studies and policy reports reveal significant gaps in legal recognition, professional training, and tailored support mechanisms, leaving many victims without effective protection or pathways to rehabilitation. Drawing on existing empirical studies, legal analyses, and comparative international models, this article presents economic violence as a structural social problem rather than a private relational issue. It examines the phenomenon through ethical lenses of human dignity, social welfare, and human rights, highlighting the state’s moral responsibility to address systemic forms of control that perpetuate inequality and harm. The article further outlines policy directions emphasized in the literature, including public awareness, legal reform, economic protection measures, and long-term support systems, while acknowledging cultural, political, and resource-related challenges to implementation. By bringing economic violence out of invisibility, this article argues that addressing financial control within intimate relationships is essential not only for protecting individuals but also for strengthening democratic values, social justice, and collective well-being.